2014
DOI: 10.1103/physrevlett.113.103601
|View full text |Cite
|
Sign up to set email alerts
|

On-Chip Generation and Manipulation of Entangled Photons Based on Reconfigurable Lithium-Niobate Waveguide Circuits

Abstract: A consequent tendency toward high-performance quantum information processing is to develop the fully integrated photonic chip. Here, we report the on-chip generation and manipulation of entangled photons based on reconfigurable lithium-niobate waveguide circuits. By introducing a periodically poled structure into the waveguide circuits, two individual photon-pair sources with a controllable electro-optic phase shift are produced within a Hong-Ou-Mandel interferometer, resulting in a deterministically separated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
173
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 291 publications
(177 citation statements)
references
References 38 publications
3
173
0
1
Order By: Relevance
“…Correlated photon pairs are an important resource for quantum photonics that can be generated on-chip by quantum dots [4] or integrated nonlinear waveguides [5,6,14]. As well as being both compact and efficient, integrated photon pair sources have also shown unprecedented versatility in tailoring the properties of the generated twin-photon state through dispersion engineering and birefringence management, thereby establishing control over the spectral and polarization entanglement [15][16][17], photon bandwidths [18], and degree of non-degeneracy.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Correlated photon pairs are an important resource for quantum photonics that can be generated on-chip by quantum dots [4] or integrated nonlinear waveguides [5,6,14]. As well as being both compact and efficient, integrated photon pair sources have also shown unprecedented versatility in tailoring the properties of the generated twin-photon state through dispersion engineering and birefringence management, thereby establishing control over the spectral and polarization entanglement [15][16][17], photon bandwidths [18], and degree of non-degeneracy.…”
Section: Introductionmentioning
confidence: 99%
“…In much the same way, quantum interference between two identical sources of photon pairs can be used to achieve the reverse effect: the anticoalescence of bunched states into anti-bunched states. Such interference-facilitated pair separation (IFPS) was realized first in fiber Sagnac loops [22][23][24] and more recently on-chip [12,14] by coherently pumping two photon pair sources, e.g. denoted A and B, to create an approximate NOON-type state of the form |Ψ = |ψ A |0 B + e iθ |0 A |ψ B where θ represents a stable relative phase, |ψ a photon pair, and |0 the vacuum.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome this limitation, in this paper, authors have demonstrated the design for an optical counter based on electro-optic (EO) effect of LiNbO 3 based Mach-Zehnder interferometer (MZI). LiNbO 3 based MZI is characterized by the attractive features of compact size, thermal stability (Wooten et al 2000), re-configurability (Jin et al 2014), integration potential (Wooten et al 2000), low latency and low power consumption (Singh et al 2012;Kumar et al 2015b). Due to which many researchers have shown their keen interest and designed various combinational and sequential circuits using MZIs (Kumar et al , 2014a(Kumar et al , b, 2015aRaghuwanshi et al 2013Raghuwanshi et al , 2014.…”
Section: Introductionmentioning
confidence: 99%
“…Due to variation of the refractive index, the phase difference arises, and depending upon the phase, signal shifts from one waveguide to another waveguide. LiNbO 3 based MZI is characterized by the attractive features of compact size, thermal stability (Wooten et al 2000), re-configurability (Jin et al 2014), integration potential (Wooten et al 2000), low latency and low power consumption (Singh et al 2012;Kumar Kumar et al 2015b). Due to which many researchers have shown their keen interest and implemented various combinational and sequential circuits using MZIs (Kumar et al , 2014a(Kumar et al , b, 2015aRaghuwanshi et al 2013Raghuwanshi et al , 2014.…”
Section: Introductionmentioning
confidence: 99%